Application of Caputo-Fabrizio Fractional Order Derivative (NFDt) in Simulating the MHD Flow of the Third Grade non-Newtonian Fluid in the Porous Artery - Uddin, Salah; Mohamad, M.; Sufahani, Suliadi; Ghazali Kamardan, M.; Ullah Mehmood, Obaid; Wahid, Fazli; Roslan, R. (International Journal of Engineering and Technology, 2018)
In this paper, the third grade non-Newtonian MHD blood flow in the porous arteries subjected to the periodic pressure gradient was studied using the Caputo-Fabrizio (NFDt ) time fractional order derivative. The time fractional model was solved by taking the Laplace and the finite Hankel transforms. Results were compared with those reported in the previous studies and good agreement was found. The Mathematica software was used to simulate the velocity profile and the Bessel functions with zero order and first order of first kind. The correlations between the flow velocity and the third grade non-Newtonian fluid parameter, the magnetic field and the porosity were negative. Nevertheless, the flow velocity increased with respect to the Womersely number.Â Â